Altered mRNA splicing in monkey cells abortively infected with human adenovirus may be responsible for inefficient synthesis of the virion fiber polypeptide. - Anderson, K P (1984)
Messenger RNA encoding the fiber protein of the human adenovirus serotype 2 (Ad2) capsid is inefficiently translated in abortively infected African green monkey kidney cells. The amount of fiber mRNA present in the cytoplasm of abortively infected monkey cells is less than that in productively infected cells by a factor of 5-10 but synthesis of the fiber polypeptide is reduced by a factor of more than 100. Evidence from a variety of experiments indicates that the defect does not lie in the translational apparatus of the monkey cell but may best be explained by differences in the fiber messages made in abortively versus productively infected cells. Here we report that fiber mRNA isolated from abortively infected monkey cells is processed differently than that made in productively infected cells. Primer extension analysis of the 5' ends of fiber messages from several different productive and abortive infections shows a direct correlation between synthesis of the fiber polypeptide in vivo and the presence of the "x" and/or "y" ancillary leaders on messages encoding the fiber polypeptide. Of all the mRNAs encoded by the major late transcriptional unit of Ad2 only the fiber message can contain the x and y leaders, and the fiber protein is the only late Ad2 protein reported to be glycosylated. We speculate that these leader sequences play a role in the synthesis of this glycoprotein, as well as that of the Ad2 19-kilodalton glycoprotein encoded by early region 3, whose mRNA also contains the x and y leaders.